2021
DOI: 10.3389/fphar.2021.729890
|View full text |Cite
|
Sign up to set email alerts
|

The Positivity Rate of IA-2A and ZnT8A in the Chinese Han Population With Type 1 Diabetes Mellitus: Association With rs1143627 and rs1143643 Polymorphisms in the IL1B Gene

Abstract: Objective: To investigate the association between susceptibility to type 1 diabetes mellitus (T1DM) and polymorphisms (rs1143627 and rs1143643) in the interleukin 1 beta (IL1B) gene in the Chinese Han population.Methods: The Meso Scale Discovery (MSD) method was used to detect the concentration of IL-1β in 24 T1DM patients and 27 healthy controls. MassARRAY was used to analyze the polymorphisms in the IL1B gene in 510 patients with classic T1DM and 531 healthy controls. The general data of the T1DM patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The concentration of IL-1β in T1DM patients was significantly higher than that in healthy controls. Osman A. E. et al, 2021 [22] IL levels in T1DM were higher than controls. Tangjittipokin W. et al, 2021 [24] IL1B SNPs are associated with T1DM susceptibility.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The concentration of IL-1β in T1DM patients was significantly higher than that in healthy controls. Osman A. E. et al, 2021 [22] IL levels in T1DM were higher than controls. Tangjittipokin W. et al, 2021 [24] IL1B SNPs are associated with T1DM susceptibility.…”
Section: Discussionmentioning
confidence: 91%
“…IL-1 and its SNPs were investigated by Li J. et al [22], more specifically, the authors of the study measured the concentration of IL-1β, a pro-inflammatory cytokine, in the blood of patients with T1DM and healthy controls. They found that the concentration of IL-1β was significantly higher in patients with T1DM compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with IA-2A tend to be younger, have lower fasting and stimulated C-peptide levels, and experience a shorter duration of symptoms. Some immune-associated variants, such as in IL27 , IFIH1 , and CTLA4 , have been linked to the presence of IA-2A [ 27 29 ]. However, there is significant variability in the rate of pancreatic β cell destruction, which may be caused by genetic susceptibility [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility is likely to play a significant role in it. Several studies have identified correlations between immune-related variants and the positive rate of islet autoantibodies, such as IL27-IA2A, IFIH1-IA2A, IL2RA-GADA, IL1B-ZnT8A, and CTLA4-IA2A ( 15 , 42 , 43 ). Our results confirm an association between PRRC2A risk alleles and islet autoantibody positivity.…”
Section: Discussionmentioning
confidence: 99%